Randomized controlled trial evaluating a novel community eye care programme for elderly individuals with visual impairment. (12th January 2018) - Tan, Anna CS; Man, Ryan; Wong, Chee Wai; Lee, Shu Yen; Lamoureux, Ecosse L; Ang, Marcus
Abstract: Importance: The novel intervention was effective at improving compliance to appropriate tertiary eye care after community eye screening. Background: Elderly individuals from low socio‐economic background with visual impairment (VI) often do not attend tertiary care, even if significant eye diseases are detected while in the community. We evaluate a novel incentive care scheme (ICS) to improve compliance to appropriate follow‐up after community eye screening. Design: Randomized controlled trial in a population‐based setting was conducted. Participants: A total of 140 elderly individuals with VI (visual acuity <6/12, mean age ± SD = 66.6 ± 8.9 years, 46.4% female) were included. Methods: Participants were randomized to either ICS ( N = 72) or usual care (UC; N = 68). ICS incorporated patient education, social support and financial assistance to assist individuals in attending tertiary eye care. UC comprised of a standard referral letter and advice. Main outcome measure: Primary outcome included compliance to eye care referral. Secondary outcomes included best‐corrected visual acuity and vision‐related quality of life assessed at baseline and 3 months. Results: Participants receiving the ICS intervention had higher rates of compliance to tertiary eye care attendance compared to UC (31.9% vs . 16.2%, respectively, P = 0.027). While we observed an overall significant improvement in best‐corrected visual acuity at 3 months in both groups ( P < 0.05), we found no significant differences in Rasch‐transformed vision‐related quality of life scores between groups (all P > 0.05). Identified barriers for tertiary healthcare access included patient attitudes and financial‐ and health‐related barriers. Conclusion and Relevance: Our pilot RCT found that ICS improved adherence to appropriate tertiary eye care referrals after community eye screening in elderly people with VI.